Magic and the Communist Revolt of 1926 in Banten: - Ulumi, Helmy Faizi Bahrul (Kawalu: Journal of Local Culture, 2015)
Studies on magic in civil revolts in Indonesia are remarkably scarce. The use of magic in Bantenese revolts are presented in the works of Kartodirdjo (1966) and Williams (1982,1990). This article explains several aspects of magic such as the form, the ritual, and thesources related to magic sourced from the Script of K.H. Muqri Labuan, one of the important figures in the communist revolt of 1926 in Banten, by using philological and historical approaches. The Script was written byK.H. Muqri during his escapee from Surabaya to Mecca when the Dutch colonial could defeat his rebellion in Labuan. His script is 17,5x21 cm consisted of 540pages written in Jawiand Arabic.  It mostly contains the magical formula and wird of severaltariqa. It also comprises his genealogy, the magical licence (ijÃ¢zah)he obtained, his journey notes to Mecca, his activities during living in Mecca, and the list of his disciples. Keywords: Banten, Magic, Tariqa, Social Revolution, Communism